100 Years of Human Factors/Ergonomics at Purdue University. (January 2016) - Proctor, Robert W.; Kim, Sung-Hee
Human factors/ergonomics (HF/E) has a 100-year history at Purdue University. Frank and Lillian Gilbreth exerted considerable influence on the development of HF/E at Purdue during its first 50 years. Their interdisciplinary approach is evident in the programs of the School of Industrial Engineering and the Department of Psychological Sciences as well as in the many individuals in other departments who have interests in HF/E. Although there has been a shift toward cognitive ergonomics in the past 50 years, the interdisciplinary legacy of the Gilbreths continues to be relevant to research, education, and application in HF/E in the 21st century.